Evaluación de una plantación de Simarouba amara “Marupa”, CIEFOR - Puerto Almendra, Loreto – Perú. 2021 - Andrade Del Aguila, Jessel Katherine (2023)
The study was carried out in the Forest Plot No. 21 of CIEFOR – Puerto Almendras. The population was a total of 200 Simarouba amara plants. Biometric measurements of diameter, height, quality, phytosanitary status and survival of the plants were made in 4 months of evaluation. The average increase in diameter in the Simaouba amara plantation was 0.36 mm. The planta tion presented an average increase in height of 13.52 cm. There is a survival of 90.5% (181 live plants), while mortality reached 9.5% (19 dead plants). 76.9% of the plants have Good quality (153 plants), followed by Regular quality with 13.1% (26 plants) and finally BAD quality obtained 1% (2 plants). A total of two plants were affected up to 80% of the leaf area, while 26 plants presented 50% of the leaf area affected and 153 plants did not show signs of pests and diseases. According to the analysis of variance, there is no significant difference between the average increases in diameter and height and the strips. It is necessary to carry out similar studies with other native forest species in CIEFOR - Puerto Almendras.